Formation of Allenes by 1,4-Addition of Intermolecular Phosphane/Borane Frustrated Lewis Pairs to a Conjugated Enyne - Feldhaus, Philipp; Wibbeling, Birgit; Fröhlich, Roland; Daniliuc, Constantin G.; Kehr, Gerald; Erker, Gerhard (Synlett, 2014)
The t-Bu3P/B(C6F5)3 frustrated Lewis pair (6a) undergoes competing acetylene deprotonation (to give the phosphonium–alkenylborate salt 8) and 1,4-P/B FLP addition to the conjugated enyne 2-methylbutenyne to yield the zwitterionic allene derivative 9a. The less basic (o-tolyl)3P/B(C6F5)3 system (6b) avoids the acetylene deprotonation pathway. The zwitterionic allene derivative 9b formed by 1,4-P/B FLP addition to the enyne is again a prominent reaction product; here competing 1,2-addition is observed to give the olefinic product 10. The allene derivatives 9a and 9b and their competing products 8 and 10 were characterized by X-ray diffraction.
Keywords: phosphorus; boron; Lewis pairs; allenes